Bacillus Spizizenii FMH45-based biofertilizer enhances growth and halotolerance of cherry tomato plants under hydroponic cultivation systems - Fatma Masmoudi; Imen Saadaoui; Saoussen Ben Khedher; Saoussen Ben Khedher; Slim Tounsi (Frontiers in Sustainable Food Systems)
IntroductionHydroponic cultivation systems using desalinated groundwater may play pivotal role in reducing freshwater consumption for irrigation. However, reliance on desalination remains unsustainable due to its high cost, energy demand, and the serious environmental impacts of its brine byproducts. Producing a biofertilizer that enables groundwater irrigation in hydroponics by enhancing plant halotolerance and resistance to salt stress offers a promising solution to address freshwater scarcity and low soil quality in arid and semi-arid regions, such as the Arabian Gulf.MethodsThis study investigates the potential of Bacillus spizizenii FMH45 in field experiment to enhance tomato plant production under greenhouse cultivation in hydroponics using directly groundwater for irrigation without desalination.Results and discussionResults demonstrated that the FMH45-based biofertilizer (HB45) significantly improved plant physiological parameters under greenhouse conditions. These improvements included a notable increase in shoot elongation (>13%), enhanced SPAD index values (>8%), and significant rises in flower and fruit counts (≃ 11% and 22%, respectively). B. spizizenii HB45 showed significant potential to increase bacterial densities by over 100-fold in various plant organs under saline irrigation and prevent salt infiltration into internal plant tissues. Furthermore, HB45-treatment enhanced the plant oxidative stress response as evidenced by stable catalase activity, an approximately 50% reduction in lipid peroxidation markers such as malondialdehyde (MDA), and a 35% decrease in reactive oxygen species (ROS), including hydrogen peroxide (H2O2). These findings demonstrate that B. spizizenii FMH45 holds significant potential for the development of effective biofertilizers capable of mitigating salt stress while boosting crop productivity. This approach offers a sustainable alternative to desalination-dependent hydroponics, particularly for arid and semi-arid regions, including Qatar.